Analysis of the mechanism regulating the killing effect of EBNA1 on EBV-associated B-cell tumors: Effect of EBNA1 on EBV-associated B-cell Tumors - Zhang, Zhan; Tang, Xiaowan; Li, Jianhua; Yang, Qiao (Cellular and Molecular Biology, 2022)
In order to analysis of the mechanisms regulating EBNA1 killing of EBV associated B cell tumors, preparations were first made for EBV-associated B cells, and the cells were subsequently transformed. The killing effect of ebna1-28 T cells on EBV-positive B cell lymphoid tumor cells was detected using the FACS method. SF rats were also selected to analyze the inhibitory effect of ebna1-28t on transplanted tumors in nude mice with EBV-positive B cell lymphoma. Results showed that compared with the untransfected group, the expression of EBNA1 was higher in the empty plasmid SFG group, the recombinant plasmid rv-ebna1/car group compared with the empty plasmid SFG group, and the expression of EBNA1 was higher in the untransfected group compared with the empty plasmid SFG group, which was statistically significant (P < 0.05); As shown in Figure 1, in vitro studies found that, compared to the untransfected group, the empty plasmid SFG group, the recombinant plasmid rv-ebna1/car group showed better killing efficacy on Raji cells, and the recombinant plasmid rv-ebna1/car group showed better killing efficacy on Raji cells compared to the empty plasmid SFG group; The tumor volumes of the rats in group C were larger compared with those in groups A and B, and the tumor volumes of the rats in group A were smaller compared with those in group B. The tumor volumes of the rats in group C were larger compared with those of the rats in the three groups (P<0.05). In group C, the cells were more severely invaded, and the nuclei were damaged. In group B, cell invasion in tissues was mild in the nucleus. The infection of cells in the tissues of rats in group A was better compared to groups B and C. In vitro experiments found that inhibition of EBNA1 was able to kill EBV-positive B cell lymphoid tumor cells effectively. Animal experiments found that ebna1-28t was able to shrink the volume as well as tumor weight of transplanted tumors in nude mice with EBV-positive B cell lymphoma and played a better inhibitory role.